FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA PELAJARAN EKONOMI SMK MUHAMMADIYAH 2 PEKANBARU - Putri Clawson; Mayang Mawaddah Yarsad (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2015)
The purpose of this study was to determine the factors that influence students' motivation in class X Adp 3 in economic subjects at SMK Muhammadiyah 2 Pekanbaru to analyze and determine the effect of student personal variables (X1) teacher's personal (X2) Network Structure of Social Relations in Schools (X3) and Schools as Educational Institutions (X4) on learning motivation (Y). In this study data were collected through questionnaire distribution to 32 Class X Adp 3 students at SMK Muhammadiyah 2 using the saturation sampling method. The method used in this research is quantitative descriptive analysis. Quantitative analysis includes validity and reliability tests, classic assumption tests, hypothesis testing through the F test and t test and test. The results of the analysis found that the four independent variables namely students' personal (X1) personal teacher (X2) Network Structure of Social Relations in Schools (X3) and Schools as Educational Institutions (X4) had a positive and significant influence on learning motivation (Y). Hypothesis testing using the t test shows that the two independent variables studied were proven to significantly affect the dependent variable of student learning motivation. Then through the F test it can be seen the value of f arithmetic 14.236 with a significance level of 0.000 that the four independent variables significantly influence together on student motivation.